Prolonged Drainage and Intrapericardial Bleomycin Administration for Cardiac Tamponade Secondary to Cancer-Related Pericardial Effusion. Issue 15 (April 2016) - Numico, Gianmauro; Cristofano, Antonella; Occelli, Marcella; Sicuro, Marco; Mozzicafreddo, Alessandro; Fea, Elena; Colantonio, Ida; Merlano, Marco; Piovano, Pierluigi; Silvestris, Nicola
Abstract : Abstract: Malignant pericardial effusion (MPE) is a serious complication of several cancers. The most commonly involved solid tumors are lung and breast cancer. MPE can give rise to the clinical picture of cardiac tamponade, a life threatening condition that needs immediate drainage. While simple pericardiocentesis allows resolution of the symptoms, MPE frequently relapses unless further procedures are performed. Prolonged drainage, talcage with antineoplastic agents, or surgical creation of a pleuro-pericardial window are the most commonly suggested ones. They all result in MPE resolution and high rates of long-term control. Patients suitable for further systemic treatments can have a good prognosis irrespective of the pericardial site of disease. We prospectively enrolled patients with cardiac tamponade treated with prolonged drainage associated with Bleomycin administration. Twenty-two consecutive patients with MPE and associated signs of hemodynamical compromise underwent prolonged drainage and subsequent Bleomycin administration. After injection of 100 mg lidocaine hydrochloride, 10 mg Bleomycin was injected into the pericardial space. The catheter was clumped for 48 h and then reopened. Removal was performed when the drainage volume was <25 mL daily. Twelve patients (54%) achieved complete response and 9 (41%) a partial response. Only 1 (5%) had a treatment failure and underwent a successful surgical procedure. Acute toxicity was of a low degree and occurred in 7 patients (32%). It consisted mainly in thoracic pain and supraventricular arrhythmia. The 1-year pericardial effusion progression-free survival rate was 74.0% (95% confidence interval [CI]: 51.0–97.3). At a median follow-up of 75 months, a pericardial progression was detected in 4 patients (18%). One- and two-year overall survival rates were 33.9% (95% CI: 13.6–54.2) and 14.5% (95% CI: 0.0–29.5), respectively, with lung cancer patients having a shorter survival than breast cancer patients. The worst prognosis, however, was shown in patients not suitable for systemic treatments, irrespective of the site of the primary tumor. Prolonged drainage and intrapericardial Bleomycin is a safe and effective treatment, which should be considered as first choice at least in patients suitable for active systemic treatment.